Neural signatures of atypical social brain development in autism - Pelphrey, Kevin (Henry Stewart Talks, 2010)
The social brain, Regional localization of areas involved in social perception, What brain mechanisms support recognition of biological motion?, Posterior STS region, Does the posterior STS exhibit differences in activity that depend on the previous emotional context related to understanding other's preferences?, Eye-gaze processing deficits in autism, Can we normalize FFG activity in participants with autism by experimentally modifying visual scanpaths?, Insights from the developing social brain, Behavioral training for fMRI, Does the STS respond selectively to biological motion in children with autism?, The development of brain mechanisms for emotion regulation in children with and without autism